A Novel Oxidant For Nickel Hydrometallurgy - V. A. Ettel; M. A. Mosoiu; E. A. Devuyst (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1981)
Nickelic hydroxide is an important metallurgical reagent used for precipitating cobalt from nickel sulfate solutions. Existing methods of preparation of nickelic hydroxide involve electrolytic oxidation of Ni(OH)2 or the use of strong oxidizing agents such as chlorine, ozone and persulfate. Although the oxidizing properties of the SO2 + O2 system have been known for some time, e.g., detection of SO2 and oxidation on iron in acidic solution, the application of this system for the preparation of nickelic hydroxide as a process was not considered in the past. The present paper describes a new method for chemical preparation of nickelic hydroxide which has been developed in INCO laboratories. The technique consists of reacting nickelous hydroxide suspensions with a slurry of calcium sulfite in the presence of air or oxygen. The main advantage of the process is the cost of reagents and an absence of soluble by-products (e.g., C1-). The chemistry of this process is unusual since the redox potential obtained during the reaction exceeds that of the oxygen electrode. Therefore, the effect of CaS03 is not just a catalytic acceleration of the reaction NI(OH)~ + 02. The so3= must be involved in the stoichiometry of the overall reaction producing in the initla1 phase some strongly oxidizing intermediate species.